Stranden og havet: Lyserød imperialisme og markedspladser i ”Det store Ocean” - Andersen, Frits (K&K - Kultur og Klasse, 2017)
The Marquesas Islands, one of the Pacific’s smallest and most remote archipelagoes, played an important geopolitical role in the years around the French Revolution because they were attributed a symbolic significance as the hub of crossing trade routes between Europe, North America, and China. The fur trade became an essential part of the performative identity games, which ethno-historian Greg Dening has called “beach crossings”. The commodity is of course an essential part of the exchange on the beach, but the trade also defines the meaning of the involved places and spaces in a broader sense. On the basis of comparisons of especially French expeditions to the islands, the article finds a distinctive discursive pattern: The texts develop an idea of The Great Ocean as utopian theater that shapes the form of trade and colonization, which can be called “pink imperialism”, ie. annexation, trade, and commerce as an act of protection or an act of love.